‘Pandora’s box’ of the developing world-perioperative implications of pulmonary infections - Khanna, Sangeeta; Das, Jyotirmoy; Mehta, Yatin; Khan, Ali Zamir (Video-Assisted Thoracic Surgery; Vol 2 (August 2017): Video-Assisted Thoracic Surgery, 2017)
Infective pathologies of the lung such as tuberculosis, aspergillosis, hydatid cyst, empyema thoracis etc. are quite prevalent in the developing countries of the world and their sequelae are the norm rather than the exception. Poor financial resources and lack of adequate healthcare facilities in the third world add to the compendium of healthcare problems faced by the general population. They have their unique share of pulmonary diseases not otherwise encountered routinely in the western world. Lack of screening facilities allows these diseases to progress unnoticed. Often the first presentation in the hospital is when the disease has advanced and the management is challenging. A significant percentage of these patients are then referred to the thoracic surgeon for definitive management. These include chest drain insertion, thoracoscopy, decortication, segmentectomy, lobectomy or pneumonectomy. Lung isolation and management of one lung anaesthesia are fundamental to thoracic surgery practice. But trained thoracic anaesthesiologists with expertise in dealing with such high-risk procedures and physicians with good ICU backup to look after the patient during the perioperative period are mainly concentrated in the large government and private hospitals of metro cities. Smaller hospitals and cities do not have access to a good thoracic surgeon. General surgeons perform most thoracic procedures. Due to mismatch of equity, straightforward cases that can be managed surgically are management conservatively with a trial of medical therapy. Referral for surgery is delayed leading to advanced cases with irreversible lung damage. Our article deals with the problem of infective pathologies of the lung especially in reference to the developing world and their perioperative management concerns and the role of video assisted thoracic surgery in such scenarios.